2019
DOI: 10.3389/fpsyg.2019.00990
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Motivational Profiles in Mathematics and Science: Associations With Achievement Striving, Career Aspirations and Psychological Wellbeing

Abstract: Pertinent to concern in Australia and elsewhere regarding shortages in STEM fields, motivational expectancies and values predict STEM study and career aspirations. Less is known about how “cost” values may deter, and how expectancies/values and costs combine for different profiles of learners to predict achievement aspirations and psychological wellbeing outcomes. These were the aims of the present study using established measures of perceived talent, intrinsic and utility values, and a new multidimensional “c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 101 publications
15
69
0
Order By: Relevance
“…As has been noted in previous research, students aiming to succeed well often do but are also susceptible for negative effects on well-being (e.g., Tuominen-Soini et al, 2011. These findings reflecting the differences between mastery-and success-oriented students echo the results of Watt et al (2019), who identified Positively engaged (i.e., high on expectancy-value constructs, low on costs) and Struggling ambitious (i.e., high on positive values and costs) students, who differed in that the Struggling ambitious students perceived high costs, accompanied with debilitated psychological well-being, but still no impairment in achievement striving.…”
Section: Subject-specific Achievement Goal Orientation Profiles Assocsupporting
confidence: 76%
See 3 more Smart Citations
“…As has been noted in previous research, students aiming to succeed well often do but are also susceptible for negative effects on well-being (e.g., Tuominen-Soini et al, 2011. These findings reflecting the differences between mastery-and success-oriented students echo the results of Watt et al (2019), who identified Positively engaged (i.e., high on expectancy-value constructs, low on costs) and Struggling ambitious (i.e., high on positive values and costs) students, who differed in that the Struggling ambitious students perceived high costs, accompanied with debilitated psychological well-being, but still no impairment in achievement striving.…”
Section: Subject-specific Achievement Goal Orientation Profiles Assocsupporting
confidence: 76%
“…Collating the previous research together and drawing particularly from Daniels et al (2008) , Tuominen-Soini et al (2008 , 2012) , Luo et al (2011) , Lo et al (2017) , and Jiang et al (2018) students with profiles high in mastery were anticipated to demonstrate adaptive well-being (e.g., low cost, high engagement, low burnout), students with profiles high in both mastery and performance were anticipated to demonstrate maladaptive along with adaptive well-being (e.g., high cost, high engagement, high exhaustion), students with profiles characterized by average scores on all orientations were anticipated to show moderate well-being (e.g., average cost, engagement, and burnout), and students with profiles high on avoidance goals were anticipated to demonstrate maladaptive academic well-being (e.g., low engagement, high cynicism), that is, as suggested by Watt et al (2019) , besides the consistently adaptive (e.g., mastery-oriented) and maladaptive (e.g., avoidance-oriented) profiles, we also expected to find asynchronous profiles (e.g., success-oriented), in which not only achievement goals but also costs would be high and which might further exert some deleterious effects on academic well-being (e.g., high emotional exhaustion and stress; see also Tuominen-Soini et al, 2008 ), regardless of high engagement ( Tuominen et al, 2020b ).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Little research has been conducted in education on motivational profiles using the person-centered approach (Gillet, Morin, & Reeve, 2017). Prior studies fusing student motivation with studentcentered analyses have focused on the expectancy-value framework (Watt, Bucich, & Dacosta, 2019); achievement goal-orientation (Tuominen-Soini, Salmela-Aro, & Niemivirta, 2011; need achievement (Covington & Omelich, 1991); burnout and engagement (Salmela-Aro & Read, 2017); and combinations of adaptive/maladaptive motivation, self-regulation, and psychological wellbeing (Elphinstone & Tinker, 2017). Among the research that has focused on the multidimensionality of motivation, the most prominent in the academic context has primarily been carried out from the self-determination framework (Deci & Ryan, 2000).…”
Section: Theoretical Backgroundmentioning
confidence: 99%